From Friction to Acceleration: China’s Ambition for a Post-Pandemic Tianxia World Order - Demas Nauvarian; Filasafia Marsya Ma'rifat (Global South Review, 2021)
This paper explores the relation between the Covid-19 pandemic and China’s peaceful rise. In March 2020, the Covid-19 virus outbreak was declared by World Health Organization (WHO) as a global pandemic that knows no boundaries. While China received an enormous spotlight for being the ground-zero of the pandemic, China has managed to control the pandemic effectively. Not only that, China has also even been able to help other countries by providing Covid-19 assistance to other countries in need. More significantly, however, China was in a unique position when the pandemic hit—it was in a critical period for its rising era. China’s rise has been framed as a ‘peaceful rise’ (heping jueqi). On the other hand, the pandemic forced China to re-think its national power usage while still striving to achieve an idealized order of Tianxia—all-under-heaven. This research analyses how China’s pandemic cooperation is utilized in a greater framework of peaceful rise to accelerate the establishment of Tianxia world order. This research argues that the pandemic served as a critical juncture for the status-quo liberal international order, and China took the opportunity to indirectly disrupt the order. This is evident through two main pillars of China’s pandemic cooperation: (1) asserting self-reliance by strengthening national response; (2) establishing cooperation to put China as a ‘middle kingdom.’ This research concludes that China, in some ways, successfully transform the pandemic from friction to an acceleration factor for its peaceful rise.